Uptown cigarette - Derry, Robin, (SAGE Knowledge. Cases., 2017)
After several years of losing market share to competitors, former industry giant RJ Reynolds (RJR) decides to regain strength through new brands targeting demographic segments that still show significant growth potential. As RJR prepares to launch a cigarette designed and marketed explicitly to black consumers, several community health groups join forces to protest it. When Health and Human Services Director Louis Sullivan asks RJR Chief Executive Officer Jim Johnston to withdraw the brand from the market, RJR needs to formulate an appropriate and socially acceptable response.